Interaction of insulin with Pseudomonas pseudomallei. - Woods, D E (1993)
Pseudomonas pseudomallei is the causative agent of melioidosis, a disease being increasingly recognized as an important cause of morbidity and mortality in many regions of the world. An intriguing observation regarding melioidosis is that a significant percentage of patients who develop the disease have preexisting diabetes mellitus. In this regard, we have tested the hypothesis that insulin may modulate the growth of P. pseudomallei. We have demonstrated that insulin markedly inhibits the growth of P. pseudomallei in vitro and in vivo. The growth rate of P. pseudomallei in minimal medium containing human recombinant insulin was significantly lower than that of control cultures containing no insulin. P. pseudomallei grew at an increased rate in serum samples obtained from diabetic rats compared with that in serum samples obtained from control animals. When the insulin level was restored by the addition of human recombinant insulin, the growth rate was reduced to a level similar to that seen in control serum. P. pseudomallei also grew significantly better in insulin-depleted human serum than control human serum. 125I-insulin binding studies demonstrated that P. pseudomallei possesses a specific, high-affinity binding site for human insulin. In in vivo studies, rats made diabetic by streptozotocin injection (80 mg/kg of body weight, intraperitoneally) were significantly more susceptible to P. pseudomallei septicemia than control rats. Thus, it appears that serum insulin levels may play a significant role in modulating the pathogenesis of P. pseudomallei septicemic infections.